Individual participant data (IPD) meta-analysis: An introduction – Narrative review - Ekta Rai; Vibhavari Naik; Aparna Williams; Mohan S. Kamath (Indian Journal of Anaesthesia)
Systematic reviews and meta-analyses (MA) are accepted modalities for evidence synthesis in evidence-based medicine. However, as MA uses aggregate data that includes averaging patient characteristics and pooled effect estimates, it has limitations when considering personalised medicine. In contrast, individual participant data meta-analysis (IPD-MA) includes and segregates individual patient data to study new outcomes, identify outcome predictors, and analyse multiple covariate effects on treatments. IPD-MA requires data from multiple investigators, review board approvals, clear communication with collaborators, and statistical recalculation of cumulative data. IPD-MA can be performed as a single-stage process where data from all included studies is pooled and reanalysed or as a two-stage process where additionally the data from individual studies is re-analysed before being pooled. This review aims to orient clinicians about IPD-MA, including the process of performing it, comparing it with other types of meta-analyses and considering the potential barriers in conducting it.